Kepercayaan Sebagai Jembatan: Menggali Hubungan Antara Kemudahan Penggunaan Dan Keamanan Dalam Niat Menggunakan - Budi Santoso; Jekti Rahayu (Universitas Muhammadiyah Malang, 2024)
Purpose: The purpose of the study is to examine how trust influences users' intentions to use by mediating perceived security and convenience of use. Methodology/approach: The population in this study is all users using Kopra by Mandiri Tapal Kuda Region, East Java in 2024. Based on the results of sample calculations using G*power, the minimum sample size is 472 respondents, so the researchers used 500 respondents using the proportional random sampling method or random sampling. The Structural Equation Model (SEM) is the data analysis tool used in this study. Findings: Trust and intention to use are positively impacted by perceived security and convenience of use. Use intention is positively impacted by trust. Through trust, perceived security and ease of use both positively influence the inclination to use. Practical implications: The practical implications of this research are that organizations can increase the adoption rate of their services, reduce churn rates, and build long-term relationships with users through the trust built from the ease and security of services. Originality/value: trust as an intervening variable because customer trust in using Kopra by Mandiri will have an impact on increasing intentions to use Kopra by Mandiri which is supported by perceived ease of use and security.